Progression in Moyamoya Disease: Clinical Features, Neuroimaging Evaluation, and Treatment - Zhang, Xin; Xiao, Weiping; Zhang, Qing; Xia, Ding; Gao, Peng; Su, Jiabin; Yang, Heng; Gao, Xinjie; Ni, Wei; Lei, Yu; Gu, Yuxiang (Current Neuropharmacology, 2022)
Moyamoya disease (MMD) is a chronic cerebrovascular disease characterized by progressive stenosis of the arteries of the circle of Willis, with the formation of collateral vascular network at the base of the brain. Its clinical manifestations are complicated. Numerous studies have attempted to clarify the clinical features of MMD, including its epidemiology, genetic characteristics, and pathophysiology. With the development of neuroimaging techniques, various neuroimaging modalities with different advantages have deepened the understanding of MMD in terms of structural, functional, spatial, and temporal dimensions. At present, the main treatment for MMD focuses on neurological protection, cerebral blood flow reconstruction, and neurological rehabilitation, such as pharmacological treatment, surgical revascularization, and cognitive rehabilitation. In this review, we discuss recent progress in understanding the clinical features, in the neuroimaging evaluation and treatment of MMD.
Keywords: pathogenesis